Konstruksi Epistemologi Filsafat Hukum Islam untuk Ketetapan Hukum Islam tentang Pencegahan Global Warming - Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to develop an epistemological framework for Islamic legal philosophy related to the prevention of global warming. This research uses a qualitative approach with the analytical method of Islamic law. The results of the research and discussion show that global warming is a new empirical fact in the discussion of Islamic law so that an epistemological construction of Islamic legal philosophy is needed to explore wisdom and establish principles, foundations, legal objectives, principles and rules as raw materials. Islamic law regarding handling the impacts arising from global warming. This study concludes that inductive reasoning on the facts of global warming within the framework of the epistemology of Islamic legal philosophy along with deductive reasoning on the raw materials of Islamic law will give birth to provisions in Islamic law regarding the handling of global warming that are doctrinal and at the same time empirical-realistic. This research contributes to the preparation of an epistemological construction model of Islamic legal philosophy in response to various actual problems such as global warming.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersianÂ // Â TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//